2021
DOI: 10.1016/j.gpb.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

GranatumX: A Community-Engaging, Modularized, and Flexible Webtool for Single-Cell Data Analysis

Abstract: We present GranatumX, a next-generation software environment for single-cell RNA sequencing (scRNA-seq) data analysis. GranatumX is inspired by the interactive webtool Granatum. GranatumX enables biologists to access the latest scRNA-seq bioinformatics methods in a web-based graphical environment. It also offers software developers the opportunity to rapidly promote their own tools with others in customizable pipelines. The architecture of GranatumX allows for easy inclusion of plugin modules, named Gboxes, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Ge et al identified different biomarkers during Cashmere goat hair follicle development, which has implications for Cashmere goat breeding in the future [21] . Meanwhile, a webserver, GranatumX was also presented in this special issue, which enables biologists to access the latest single-cell bioinformatics methods in a web-based graphical environment [22] . On the other hand, as a method-oriented work, the computational model proposed by Zhong et al [23] can explore the gene–gene associations based on scRNA-seq data for critical transition prediction.…”
mentioning
confidence: 99%
“…Ge et al identified different biomarkers during Cashmere goat hair follicle development, which has implications for Cashmere goat breeding in the future [21] . Meanwhile, a webserver, GranatumX was also presented in this special issue, which enables biologists to access the latest single-cell bioinformatics methods in a web-based graphical environment [22] . On the other hand, as a method-oriented work, the computational model proposed by Zhong et al [23] can explore the gene–gene associations based on scRNA-seq data for critical transition prediction.…”
mentioning
confidence: 99%